Prevalencia de los trastornos de la personalidad en estudiantes universitarios de la ciudad de Medellín (2015)
ABSTRACT: The purpose of this study was to establish the prevalence of personality disorders in university students in Medellín, Colombia. The Millon Clinical Multiaxial Inventory II (MCMI-II) (Millon, 1987a) was applied to 1907 students from six universities. The mean age was 22 years old, and the age range was between 16 and 63 years old. A database was built containing the following information: socio-demographic variables, direct scores and standardized scores for each disorder, and a new variable, called “cut-off point”, was established, which categorized the “presence” or “absence” of the disorders. A descriptive analysis was carried out to determine the disorders´ prevalence and the outcome, going from the strongest to the weakest, was: Borderline Personality Disorder, Passive-Aggressive Personality Disorder, Antisocial Personality Disorder, Narcissist Personality Disorder, Schizotypal Personality Disorder, Paranoid Personality Disorder, Aggressive-Sadistic Personality Disorder, Avoidant Personality Disorder, Self-Destructive Personality Disorder, Histrionic Personality Disorder, Dependent Personality Disorder, Obsessive-Compulsive Personality Disorder and Schizoid Personality Disorder.